The use of cyclosporin in corticosteroid dependent asthma. Issue 6 (1st December 1997) - Coren, M E; Rosenthal, M; Bush, A
Abstract : Five children with severe asthma requiring at least 10 mg of prednisolone daily were treated with cyclosporin. Three were weaned from prednisolone, but one quickly relapsed. One girl had her steroid dose lowered but suffered unacceptable hirsutism and one child failed to respond. Cyclosporin may be useful in refractory childhood asthma. A prospective study is required to confirm this.